2021
DOI: 10.3389/fphar.2021.726005
|View full text |Cite
|
Sign up to set email alerts
|

Edible Bird Nest Protects the Kidney From Gentamicin Induced Acute Tubular Necrosis

Abstract: Every year, there are about 13.3 million cases of acute kidney injury (AKI). Although AKI is a preventable and treatable disease, if left untreated, it has high risk of multiple organ failure and progression to end stage kidney disease. Acute tubular necrosis (ATN) has been recognised as one of the major causes of AKI. Till to date, there is no effective supplement or medication in treating or reversing AKI. Most of the treatment strategies involve preventative measure to minimise the occurrence of AKI or to r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…EBN extracts can be divided into three groups: (1) aqueous/water extract, (2) pancreatic digest extract, and (3) enzyme hydrolysis extract. The pharmacological activities have been shown with EBN water extract, which include eye care effect (Abidin et al, 2011), chondro-protective agent for human chondrocytes (Chua et al, 2013), anti-aging, anti-inflammatory, and wound-healing activities of edible bird's nest in human skin keratinocytes and fibroblasts (Hwang et al, 2020), reno-protective (Lim et al, 2021), and enhances fertility and embryo implantation rate (Albishtue et al, 2019). Previous studies have shown that using pancreatic enzymes, the pharmacological activities of EBN extract include enhancement of bone strength (Matsukawa et al, 2011), improving learning ability and memory (Careena et al, 2018), neuroprotection in Alzheimer's or Parkinson's Disease (PD) (Yew et al, 2018), and health-enhancing and antiviral activities against influenza A virus (Haghani et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…EBN extracts can be divided into three groups: (1) aqueous/water extract, (2) pancreatic digest extract, and (3) enzyme hydrolysis extract. The pharmacological activities have been shown with EBN water extract, which include eye care effect (Abidin et al, 2011), chondro-protective agent for human chondrocytes (Chua et al, 2013), anti-aging, anti-inflammatory, and wound-healing activities of edible bird's nest in human skin keratinocytes and fibroblasts (Hwang et al, 2020), reno-protective (Lim et al, 2021), and enhances fertility and embryo implantation rate (Albishtue et al, 2019). Previous studies have shown that using pancreatic enzymes, the pharmacological activities of EBN extract include enhancement of bone strength (Matsukawa et al, 2011), improving learning ability and memory (Careena et al, 2018), neuroprotection in Alzheimer's or Parkinson's Disease (PD) (Yew et al, 2018), and health-enhancing and antiviral activities against influenza A virus (Haghani et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The saliva hardens, forming a half bowl that sticks to the wall (Utomo et al, 2015). Edible bird nest contains high-quality food substances that are believed to be able to overcome stomach problems, improve kidney function, increase libido, relieve asthma, cure tuberculosis, boost the body's immune system, speed up wound healing and surgery, increase metabolism, and improve concentration (Aswir and Wan, 2010;Hobbs, 2004;Lim et al, 2021;Ningrum, 2021;Roh et al, 2012;Saimah et al, 2016). The EBN has many benefits, which is the reason for China's high consumption rate.…”
Section: Introductionmentioning
confidence: 99%